Implantable biomedical materials for treatment of bone infection - Shuaishuai, Wang; Tongtong, Zhu; Dapeng, Wang; Mingran, Zhang; Xukai, Wang; Yue, Yu; Hengliang, Dong; Guangzhi, Wu; Minglei, Zhang (Frontiers in Bioengineering and Biotechnology, 2023)
The treatment of bone infections has always been difficult. The emergence of drug-resistant bacteria has led to a steady decline in the effectiveness of antibiotics. It is also especially important to fight bacterial infections while repairing bone defects and cleaning up dead bacteria to prevent biofilm formation. The development of biomedical antimicrobial materials has provided us with a research direction to address this issue. We aimed to review the current literature, and have summarized multifunctional antimicrobial materials that have long-lasting antimicrobial capabilities that promote angiogenesis, bone production, or “killing and releasing.” This review provides a comprehensive summary of the use of biomedical antimicrobial materials in the treatment of bone infections and a reference thereof, as well as encouragement to perform further research in this field.